The Singaporean ones : a syntactic analysis of one in Singlish - Chow, Siew Yeng (2019)
Despite many studies being done on Singlish over the past decades (Alsagoff, 2010; Cavallaro, Ng & Seilhamer, 2014; Tan, 2017; Wong, 2015), the negative perception of Singlish as a non-legitimate variety of English still exists. This project on the Singlish word one was carried out with the aim of paving the way for Singlish in computational linguistics to being recognised by Artificial Intelligence and eventually having Singlish be more widely accepted. Head-driven Phrase Structure Grammar (HPSG) was used for its highly-structured nature, its link to computer science and its psycholinguistic plausibility (Müller, 2013). Existing literature, different corpora and native intuition were tapped into to create models of this word. From the data, one was found to have four different grammatical functions: relativising, nominalising, genitive and emphatic. It was also discovered to have many Chinese-influenced features even when the rest of the sentence follows Standard English syntax. As a result, Standard English hierarchies of classes in HPSG as in Sag et al. (2003) were used and modified accordingly to suit the Singapore English context to create different HPSG entries of the one that could account for how they behave in Singlish.